DAYA SAING DAN DAMPAK KEBIJAKAN PEMERINTAH TERHADAP USAHATANI PADI SRI DI KECAMATAN ROGOJAMPI KABUPATEN BANYUWANGI - Widyatami, Linda Ekadewi; Wiguna, Ardhitya Alam (AGRARIS: Journal of Agribusiness and Rural Development Research, 2019)
The SRI method is one approach in rice cultivation practices that emphasizes the management of land, plants and water through group empowerment and local wisdom based on environmentally friendly activities. One method of rice cultivation which was developed in Banyuwangi Regency in 2012 was System of Rice Intensification (SRI) method. One area in Banyuwangi Regency that has succeeded in developing the SRI method of rice farming is Watukebo Village in Rogojampi District. The purpose of this reserach was to determine the competitiveness and the impact of government policies on SRI rice farming in Watukebo Village, Rogojampi District, Banyuwangi Regency. The analytical method used was the Policy Analysis Matrix method, which is by calculating tradable input costs, nontradable input costs, revenue, and profits of the private price and the social price of SRI rice farming. The research sample were rice farmers who applied the SRI method which have joined in Sumber Urip Farmer Group. The results of the analysis show that the SRI method has a competitive advantage and comparative advantage. Government policies on tradable inputs and tradable output have a positive impact on SRI method, and together with the government policies on tradable inputs-output and non-tradable inputs have a positive impact on the SRI rice farming method.